Los impuestos prediales municipales y su incidencia en la solvencia del gasto público del gobierno autónomo descentralizado del cantón Quevedo, periodo 2013-2014. - Mena Córdova, Danna Geanine (2015)
The present investigation, THE MUNICIPAL PROPERTY TAX AND ITS IMPACT ON THE RELIABILITY OF PUBLIC EXPENDITURE OF HOME GOVERNMENT OF CANTON decentralized Quevedo, 2013-2014. Has the main objective, the need to understand the importance of property tax and its impact on public expenditure and investment of GAD Quevedo Canton, diagnosing the situation by the municipal administration through economic activities to improve collection, collection system, and priority needs for citizenship before the period cited. The theoretical foundation studies includes the following categories: on the economic theories of tax, economic growth, tax management, public expenditure, planning and public investment, the autonomous governments, municipal land, the municipal property tax and their respective legal base. The research results comprise the basis of surveys taxpayers rustic and urban property tax, interviews four directors of the departments of municipal, financial cadastre, revenues and income, and through direct observation to property tax taxpayers in the window of the old municipality and municipal citadel, it was possible to obtain the information necessary for verification of the hypothesis, namely: "Determining the main theoretical and legal aspects that describe the Property Tax Self-Government Decentralization of canton Quevedo, the same that is checked according to the ordinances and the law of COOTAD. COOTAD”……………..